Price Responsiveness of Factor Utilization in Swedish Manufacturing, 1870-1950 - Parks, Richard W. (The Review of Economics and Statistics, 1971)
ECONOMETRIC studies of production at the aggregate and semiaggregate levels have concentrated largely on the relation between capital and labor inputs, on the one hand, and some measure of real gross value added on the other. Studies that have gone beyond this scope to include a larger number of inputs have been confined to a highly restrictive class of production functions. Input-output studies using fixed production coefficients and studies in the agricultural field using CobbDouglas functions fall within this category.' A growing number of important economic questions, however, cannot be answered within the traditional models, but require instead a framework that allows a richer specification of the substitution possibilities among factors of production. The question of whether there are differences in the extent of substitutability or complementarity between capital and different skill categories of labor, which has been considered by Bowles [4], Cook [6], and Griliches [8], is one example where a more general production model is required. In addition, it is likely that the estimation of production parameters, in particular the elasticity of substitution (ES) between capital and labor, is biased when factors other than capital and labor are ignored. This paper presents the results of an econometric investigation of these problems using time-series data for Swedish manufacturing for the period 1870-1950. Section II presents some simple evidence that shows the extent of variation in factor output ratios in the data. Variation in these ratios is not consistent with the conditions under which the use of a valueadded production function can be justified. Section III then presents a general production model that allows the measurement of the price responsiveness of factor utilization, and section IV discusses the results of estimating the model. Finally, in section V the results of the general model are compared with the results obtained using the alternative gross value added framework and using direct production functions.